Bringing geography into the analysis of trade competition - Crespo, N.; Simões, N.; Moreira, S. (Applied Economics Letters, 2019)
Trade competition between two countries is usually measured through structural similarity indicators (e.g., Krugman Specialization Index). We contribute to the area of research that focuses on how to measure trade competition between two countries by proposing an indicator that simultaneously accounts for structural and geographical similarity (i.e., similarity in sectoral weights for each market and weights of destination markets). We develop an empirical analysis considering the exports from six European economies – France, Germany, Greece, Hungary, Sweden, and United Kingdom – to more than 120 markets. The importance of the geographical dimension is confirmed, highlighting that applied studies may produce inaccurate conclusions when this dimension is excluded.